Answer:
Step-by-step explanation:
1). x² - 8x
To convert this expression into a perfect square trinomial,
x² - 2(4x) + 4² = (x - 2)²
Therefore , 4² = 16 should be added.
Option (4) is the answer.
2). x² + 2x = 3
x² + 2(1)(x) = 3
x² + 2(1)(x) + 1 = 3 + 1 [By adding 1 on both the sides]
(x + 1)² = 4
x + 1 = ±2
x = -3, -1
Option (1) is the answer.
3). 3x²- 18x = 21
x² - 6x = 7
x² - 2(3x) = 7
x² - 2(3x) + 3² = 7 + 3²
(x - 3)² = 7 + 9
(x - 3)² = 16
x - 3 = ±4
x = -1, 7
Answer:
F,A,I
Step-by-step explanation:
What one do you need help with?
Answer:
A
Step-by-step explanation:
The base is the circle.
To find the area of the circle, use pi*r^2
pi = 3.14
r = 6
- Area = 3.14 * 6^2
- Area = 3.14 * 36
- Area = 113.04
0.05 ---> 1/18
square root of 0.25 ------> 0.05
1/7------> 0.142857 repeating
0.6 -------> 2/3